Application of STEAM Approach in Improving Science Process Skills With Lesson Study Pattern in SD Unggulan Hamzanwadi - Hariyati, Nurfathiyah; Putri, Risa Febriana; Nuraeni, Nuraeni; Uyun, Nengah Wardatul; Nurmalasari, Yulia; Irwan, Mulyadi (IJE : Interdisciplinary Journal of Education, 2024)
This study aims to improve SCIENCE process skills with the STEAM (Science, Technology, Engineering, Art, Mathematics) approach based on Lesson Study in grade 4 SD Unggulan Hamzanwadi. This research is a type of classroom action research based on Lesson Study with activity stages including Plan (Planning), Do (Implementation) and See (Reflection). The subjects of the lesson study activities were all students of grade 4 SD Unggulan Hamzanwadi in IPAS subjects. The data sources in this study are the results of observations of student activity during learning and documentation. The results of the study showed that: the implementation of the STEAM model based on lesson study can improve the science process skills of 4th grade students of Hamzanwadi Unggulan Elementary School from cycle 1 to cycle 2